Understanding the effect of acromegaly on the human skeleton. Issue 3 (3rd May 2016) - Bima, C.; Chiloiro, S.; Mormando, M.; Piacentini, S.; Bracaccia, E.; Giampietro, A.; Tartaglione, L.; Bianchi, A.; De Marinis, L.
ABSTRACT: Introduction: Acromegaly, caused in most cases by Growth Hormone (GH)-secreting pituitary adenomas, is characterized by increased skeletal growth and enlargement of the soft tissue, because GH and its effector Insulin-like Growth factor-1 are important regulators of bone homeostasis and have a central role in the longitudinal bone growth and maintenance of bone mass. Areas covered: Despite the anabolic effect of these hormones is well known, as a result of the stimulation of bone turnover and especially of bone formation, many acromegalic patients are suffering from a form of secondary osteoporosis with increased risk of fractures. Expert commentary: In this review, we summarize the pathophysiology, diagnosis, clinical picture, disease course and management of skeletal complications of acromegaly, focusing in particular on secondary osteoporosis and fracture risk in acromegaly.